2020
DOI: 10.1101/2020.03.04.976811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sox2-dependent maintenance of mouse oligodendroglioma involves the Sox2-mediated downregulation of Cdkn2b, Ebf1, Zfp423 and Hey2

Abstract: Cancer stem cells (CSC) are essential for tumorigenesis. The transcription factor Sox2 is overexpressed in brain tumors. In gliomas, Sox2 is essential to maintain CSC. In mouse high-grade glioma pHGG, Sox2 deletion causes cell proliferation arrest and inability to reform tumors in vivo;134 genes are significantly derepressed. To identify genes mediating the effects of Sox2 deletion, we overexpressed into pHGG cells nine among the most derepressed genes, and identified four genes, Cdkn2b, Ebf1, Zfp423 and Hey2,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Thus, reducing astrogliosis through cell cycle inhibition improves axonal regeneration and functional recovery after TBI (Di Giovanni et al, 2005; Zhai et al, 2022). Of note, Sox2 controls the proliferation/self‐renewal of stem cells and glial cells under both normal physiological and pathological conditions through its target genes regulatory network (Barone et al, 2021; Mercurio, Serra, & Nicolis, 2019; Zhang, Zhu, et al, 2018). Consistent with the role of Sox2 in inhibiting the proliferation of reactive astrocytes and astrocytic‐scar formation after cortical injury in the adult mouse brain (Chen et al, 2019), our results demonstrated that Sox2 deficiency in astrocytes promotes neuronal regeneration and tissue recovery after cortical injury during the early postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reducing astrogliosis through cell cycle inhibition improves axonal regeneration and functional recovery after TBI (Di Giovanni et al, 2005; Zhai et al, 2022). Of note, Sox2 controls the proliferation/self‐renewal of stem cells and glial cells under both normal physiological and pathological conditions through its target genes regulatory network (Barone et al, 2021; Mercurio, Serra, & Nicolis, 2019; Zhang, Zhu, et al, 2018). Consistent with the role of Sox2 in inhibiting the proliferation of reactive astrocytes and astrocytic‐scar formation after cortical injury in the adult mouse brain (Chen et al, 2019), our results demonstrated that Sox2 deficiency in astrocytes promotes neuronal regeneration and tissue recovery after cortical injury during the early postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…More direct evidence that NOTCH signaling could restrict glioma formation in some contexts comes from studies taking advantage of genetic conditional gene deletion or overexpression approaches in vivo. NOTCH2 overexpression can inhibit glioma formation in mouse glioma models [ 107 ] and HEY2 overexpression can reduce the proliferation of murine and human glioma cells [ 147 ]. Conversely, ID2-mediated repression of HEY1 promotes NSC transformation, possibly by releasing the expression of OLIG2 [ 148 ], an oligodendroglial lineage determinant involved in glioma cell proliferation [ 149 ].…”
Section: Notch As a Tumor Suppressor In Gliomamentioning
confidence: 99%
“…HEY2, one of the most prominent Notch pathway target genes, encodes a transcription factor [71]. Halani et al proposed that the loss of the Notch pathway activity and particularly of Hey2 levels were correlated with oligodendroglioma [72].…”
Section: Discussionmentioning
confidence: 99%